Using IoT in Double Skin Facades toward Thermal Comfort: A Review - Moazzeni Khorasgani, Ali; Niloofar Zarearsanjani; Arlyn Rodriguez (Urban Planning and Construction, 2023)
Integrating the Internet of Things (IoT) into building design and operation has ushered in a new era of sustainable architecture and enhanced occupant comfort. This paper presents comprehensive case studies focused on the application of IoT technology in the context of double-skin facades, explicitly focusing on achieving and optimizing thermal comfort. These case studies, located in an urban setting, represent a paradigm shift in architectural design principles. Double skin facades, renowned for their potential to enhance energy efficiency and occupant well-being, are further empowered through the intelligent deployment of IoT devices. This synergy between architectural innovation and digital technology is instrumental in addressing the pressing challenges of energy consumption and occupant comfort in urbanized areas. It delves into the sensors, actuators, and data analytics systems employed to monitor and control the indoor environment. Special attention is given to the dynamic adaptation of the facade system in response to real-time environmental conditions, occupancy patterns, and user preferences. One of the case studies—PH01-BRK, projects the practical application of these principles in South Dakota’s first custom passive and net-zero home, completed in 2016, using advanced thermal analysis tools, software for heating and cooling requirements, and solar data assessment. Furthermore, the paper investigates the impact of IoT-enabled double-skin facades on thermal comfort, energy efficiency, and indoor air quality within the Brookings Passive House. Quantitative data and occupant feedback are analyzed to assess the effectiveness of the IoT-driven system in maintaining optimal thermal conditions while minimizing energy consumption. The findings of this case study underscore the potential of IoT technology in revolutionizing the design and operation of sustainable buildings. It demonstrates that integrating IoT into double-skin facades can significantly enhance thermal comfort, reduce energy consumption, and create healthier indoor environments.